PEDAGOGICAL-PSYCHOLOGICAL BASIS OF THE USE OF THEORETICAL INFORMATION IN LITERARY EDUCATION - Oromova Nafosat Jo‘rayevna (American Journals, 2025)
This article provides a comprehensive analysis of psychological and pedagogical approaches aimed at effectively organizing and developing students' learning processes in teaching literary knowledge in literature lessons. Theoretical and practical principles necessary to support students' intellectual and emotional development are developed.
Keywords: Literary education, pedagogical basis, didactic principle, individual approach, psychological basis, work of art, practical approach.